Development of Assessment Instrument Android-Based Students’ Interest In Learning Mathematics SMP With CPS Model - Budi Merry Setia Ningrum, Eka; Budi Waluya, St.; Ridlo, Saiful (Journal of Research and Educational Research Evaluation, 2018)
Information about students’ interest in learning mathematic SMP as a consideration when conducting managerial evaluations which is required by the teacher, and there is no standard assessment instrument. The purpose of the study is to produce guide book of the teacher and application on android phones about an assessment instrument of students' interest based on Android on mathematics learning at junior high school CPS model with a valid, consistent, reliable and practical. The data obtained at SMP N 4 Pemalang with research subject 128 students and 7 mathematics teacher. The instrument data collector in the interview guidelines, expert validaty sheet, and questionnaires. The study used a research and development. The development model modifies the 4-D model by Thiagarajan et al. Analysis of data using triangulation sources, validity, internal consistency, reability, and confirmatory factor analysis. The results of the study showed from examine the expert team, 35 item early instrument worthy trialled. The result of 1) 32 item valid, and consistent; 2) The number of component had four factors; 3) The total of variant percentage of interest to be explained by four factors amounted to 60.016%; 4) The reliability coefficient is 0.965. The result of practicality number of instrument for teachers is 95.429 with very practical interpretations. The result of practicality number of instrument for students is 97.1 with very practical interpretations. From the result data analysis, it can be concluded that an instrument for assessing the interest of android-based student in learning mathematics for Junior High School with a Creative Problem Solving model has been valid, consistent, reliable, and practical. Product result are expected to be able to assess students’ interest.